Burden of Non-Communicable Diseases in South Asia A Clinical Review - Salehuddin, Md; Choudhury, Mamrun Nahar; Islam, Neena; Rhaman, Md Zillur; Ghosh, Shantonu Kumar; Majib, Md Shi (University Heart Journal, 2011)
Non-communicable diseases (NCDs) such as cardiovascular diseases, diabetes mellitus, cancer, and chronic respiratory diseases are on the rise in South East Asia Region (SEAR). NCDs account for nearly 54% of the deaths, significant amount of disabilities and huge socioeconomic losses in countries of SEAR. NCDs are caused by a set of behavioural risk factors, such as tobacco and alcohol consumption, physical activity and unhealthy diet (high in salt, sugar and fat and low in fruits and vegetables) and biological risk factors like raised blood pressure, raised blood sugar and impaired cholesterol levels and others. South Asia is experiencing urbanization, with widening incme and social inequities. The impact of noncommunicable diseases on the rich and the poor are likely to be different, in terms of both the principal causes and manifestations. As the rich are likely to reconnise their risk earlier and seek medical attention, they will develop chronic but manageable disease; as the poor are likely to be less aware of their risk and less able to access medical care, they will develop rapidly progressive disease with early and sudden fatal outcomes To challenge to public health is to anticipate and avert an epidemic of non-communicable diseases. NCDs risk factors can be reduced with existing knowledge through cost- effective policies and programmes, Establishment of surveillance systems for non-communicable diseases and their risk factors is essential for developing prevention strategies and monitoring the impact of control programmes. Key Words: Non-communicable diseases; South Asia; Risk factors; Burden DOI: 10.3329/uhj.v6i2.7255 University Heart Journal Vol. 6, No. 2, July 2010 pp.97-102